Frequency and factors associated with infusion-related local complications of vancomycin on peripheral venous catheters. (23rd February 2023) - Ammar, Helmi; Rolland, Simon; Jouffroy, Romain; Dubert, Marie; Le Beller, Christine; Podglajen, Isabelle; Lillo-Lelouet, Agnès; Lebeaux, David; Bensaid, Samuel
Abstract: Background: Vancomycin is a reference antibiotic against methicillin-resistant staphylococci. Its administration is associated with infusion-related local complications (IRLC). To reduce this risk, it has been proposed to increase vancomycin dilution in the IV bag and to perform continuous infusion using the volumetric pump. The aim of our study was to assess the safety of peripheral infusion of vancomycin with the volumetric pump. Objectives: To compare the frequency of IRLC between patients receiving vancomycin and those receiving β-lactam (BL) antibiotics. Our secondary objective was to assess factors associated with the occurrence of IRLC. Patients and methods: We conducted a prospective observational study in a French tertiary hospital. Between February 2021 and November 2021, we included all patients receiving continuous infusions of vancomycin or BL through a peripherally inserted venous catheter (PIVC). The primary endpoint was the occurrence of IRLC on Day 1 (D1). Results: We included 168 patients (56 vancomycin, 112 BL). At D1, 14 patients (25%) presented IRLC in the vancomycin group versus 11 patients (10%) in the BL group ( P  = 0.01). There was significantly more IRLC in the group receiving vancomycin at an infused concentration above 5 mg/mL than those receiving BL (8/15, 53.3% versus 11/112, 10%, respectively, P  < 0.01). However, no significant difference was observed between patients receiving infused vancomycin concentration ≤5 mg/mL and patients receiving BL ( P  = 0.4). Conclusion: Our data support safe administration of vancomycin if infused at a concentration under 5 mg/mL, through the volumetric pump on PIVC.